Pengaruh Kompetensi Kepribadian Guru PAK Terhadap Minat Belajar Siswa Kelas VIII SMP Negeri 3 Tarutung Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Jodi Romo Kristian Matondang; Lince Simamora; Damayanti Nababan; Oktober tua Aritonang; Simion Harianja (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
The research aims to determine the positive and significant influence of the personality competence of PAK teachers on the learning interest of class VIII students at SMP Negeri 3 Tarutung for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the personality competence of PAK teachers on the learning interest of class VIII students at SMP Negeri 3 Tarutung for the 2023/2024 academic year. Descriptive and inferential quantitative research methods. The population of all class VIII students at SMP Negeri 3 Tarutung for the 2023/2024 academic year who are Protestant Christians is 212 people. Random sampling was taken, namely 20% of the total population, namely 42 people. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value rcount=0.489>rtabel=0.304 and tcount=3.546>ttable=2.021 shows that there is a positive and significant relationship between the personality competence of PAK teachers and the learning interest of class VIII students at SMP Negeri 3 Tarutung for the 2023/2024 academic year. . b) Regression equation. c) The determination test revealed that the influence was 23.91%. d) Hypothesis testing obtained Fcount=12.566>Ftable=3.23, so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the personality competence of PAK teachers on the learning interest of class VIII students at SMP Negeri 3 Tarutung for the 2023/2024 academic year.